2D MOF nanosheets as an artificial light-harvesting system with enhanced photoelectric switching performance. Issue 11 (27th April 2022) - Liu, Lin; Lu, Xue-Ying; Zhang, Mei-Li; Ren, Yi-Xia; Wang, Ji-Jiang; Yang, Xiao-Gang
Abstract : The assembly of 2D MOF nanosheet with coumarin 6 afforded an efficient artificial light-harvesting system, which shows a high "on–off" photocurrent ratio up to 1000. Abstract : Herein, we report the synthesis, structure and photophysical properties of a novel well-defined layered metal–organic framework (MOF) [Cd(ppda)(mbib)] by the selection of two flexible ligands 1, 4-phenylenediacetic acid (ppda) and 1, 3-bis(imidazol-1-ylmethyl)benzene (mbib). A facile "top-down" sonication exfoliation method was used to break the interlayer interactions within the MOF, giving rise to 2D MOF nanosheets with ultrathin thickness and large surface areas. The integration of nanosheet donors and coumarin 6 (CM6) acceptors afforded an efficient artificial light-harvesting system, which can largely extend the absorption band from the violet to visible region. Photoelectric measurements reveal highly enhanced photoelectric switching performance with an "on–off" photocurrent ratio of up to 1000, about 33 times higher than that of pristine 2D MOF nanosheets.